2017
DOI: 10.1108/jec-01-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Community resilience through entrepreneurship: the role of gender

Abstract: Purpose This paper aims to contribute to entrepreneurship theorising by highlighting the salience of feminine caring positions in creating novel entrepreneurial roles and investigating how these roles contribute to community resilience. Using a critical feminist economics lens, alternative conceptualisations of the economy are expanded upon to reveal how an economic externality influences entrepreneurial discourse, gender roles and community resilience. Design/methodology/approach In this interpretive approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 63 publications
1
28
1
2
Order By: Relevance
“…McNaughton and Gray (2017: 3), for example, examined entrepreneurship and resilience, and emphasise that these two concepts have shared attributes, namely flexibility, adaptiveness, proactivity and innovativeness. Bakas (2017) has confirmed that entrepreneurship may increase community resilience in the context of an economic crisis. In addition, Steiner and Atterton (2015) state that rural business owners have certain characteristics (mainly motivation and resources) that help them turn challenges into entrepreneurial opportunities; thus, their influence on (community level) resilience is positive.…”
Section: Tourism Enterprises Entrepreneurship and Adaptationmentioning
confidence: 79%
See 1 more Smart Citation
“…McNaughton and Gray (2017: 3), for example, examined entrepreneurship and resilience, and emphasise that these two concepts have shared attributes, namely flexibility, adaptiveness, proactivity and innovativeness. Bakas (2017) has confirmed that entrepreneurship may increase community resilience in the context of an economic crisis. In addition, Steiner and Atterton (2015) state that rural business owners have certain characteristics (mainly motivation and resources) that help them turn challenges into entrepreneurial opportunities; thus, their influence on (community level) resilience is positive.…”
Section: Tourism Enterprises Entrepreneurship and Adaptationmentioning
confidence: 79%
“…One aspect that is missing from this study is the gender and its impact on (community) resilience (e.g. Bakas, 2017); unfortunately the data does not allow examination from that perspective.…”
Section: Discussionmentioning
confidence: 94%
“…Actualmente en Guatemala son mayoritariamente las mujeres indígenas quienes tejen y visten el vestido bordado tradicional en el telar de cintura, por lo que se establecen como las transmisoras de la memoria histórica y cultural en resistencia contra las políticas del olvido; uniendo la memoria en Guatemala con la condición de género (Méndez, 2018). El arte de tejer es una tarea normalmente considerada femenina, como lo muestra el presente caso de estudio en Guatemala (Méndez, 2018;Nelson, 2017); así como en Chipre, Europa (Kokko y Kaipainen, 2015); en Cuzco, Perú (Ypeij, 2012); en Grecia, Europa (Bakas, 2017); en comunidades diversas de México como Los Altos de Chiapas (Gil-Corredor, 2017), o Oaxaca (Ojinaga, 2020); la comunidad Seedaq, en Taiwan (Hwang y Huang, 2019); o en Sumba, Indonesia (Untari, Gajjala y Sanjaya, 2020), entre muchos otros.…”
Section: El Telar De Cintura Y El Arte De Tejer Guatemaltecounclassified
“…Collaborative networks can directly influence women entrepreneurs' HCM where collective action is encouraged among members and where members are able to access and act on learning resources, credit and group practices mobilized by the networks (Anderson, Locker, & Nugent, 2002;Woolcock, 2010). This collective action generates social capital which constitutes the shared trust, reciprocal exchanges, rules , and community development through the fostering of entrepreneurship (Bakas, 2017). For collaborative networks, the availability of capital (e.g.…”
Section: Women's Human Capital Management: the Role Of Collaborative mentioning
confidence: 99%